Potensi Panas Terbuang Kondensor AC Sebagai Sumber Pemanas Pada Cabinet Dryer - Husain Syam; Jamaluddin P.; Muhammad Rais; Nunik Lestari (Seminar Nasional LP2M UNM, 2019)
Abstract. This study aims to examine the potential of AC condenser wasted heat and compare the actual potential possessed by AC condenser wasted heat as a heating source for dryers, with its use in turmeric drying. There are two stages of testing carried out, namely testing on dryers without materials, and testing with turmeric. The no-load drying test aims to see the temperature range of the wasted heat of an AC condenser in filling a cabinet dryer. Whereas the testing with sliced turmeric aims to see the performance of the heating source in drying the material. This research was conducted by measuring the temperature of the AC condenser output in the channel between the condenser and the dryer, the plenum chamber, and the drying racks, as well as the reduction in the mass of the dried material, the moisture content, and the humidity. The results showed that the heat wasted from the AC condenser is very potential to be used to dry herbal ingredients, because drying runs in relatively low temperatures. The heat output from the condenser can reach 42.4oC and 31% of air humidity. For turmeric, drying can last for 6 hours until the material reaches a 5-6% of moisture content in accordance with the SNI standards Keywords: drying, heat, herbs, condenser, air conditioner